"Come Join Us and Lose Your Accent!”: Accent Modification Courses as Hierarchization of International Students - Ennser-Kananen, Johanna; Halonen, Mia; Saarinen, Taina (Journal of International Students, 2021)
In this article, we examine the hierarchization of international students by bringing together perspectives of linguistic legitimacy and language ideologies. Our data stems from 26 accent reduction or accent modification course descriptions and websites from U.S. universities. Based on their analysis, we discuss the sociopolitical implications of the phenomenon of these courses for international students and the ways in which language-based, particularly accent-based, arguments are used to create or reinforce different categories of students. We argue that while international students are presented as having different kinds of “comprehensibility problems” that accent modification and reduction courses are claimed to remedy, the seemingly linguistic arguments that are used for marketing do not hold. Rather, what is presented as an accent issue actually seems to be an ideological one, drawing on the students’ ethnic or geographical origins, and thereby racializing the question of language proficiency.